Occurrence of chitinolytic bacteria in shrimp rusip and measurement of their chitin-degrading enzyme activities (Biodiversitas Journal of Biological Diversity, 2017)
Puspita ID, Wardani A, Puspitasari ROA, Nugraheni PS, Putra MMP, Pudjiraharti S, Ustadi. 2017. Occurrence of chitinolytic bacteria in shrimp rusip and measurement of their chitin-degrading enzyme activities. Biodiversitas 18: 1275-1281. The objectives of this research were to isolate chitinolytic bacteria from shrimp rusip (an Indonesian traditional fermented shrimp product), identify bacterial isolates showing high chitinolytic activity, and determine the chitinolytic activity of these isolates. There were 44 chitinolytic bacteria isolated from shrimp rusip: 39 isolates of Gram-positive bacteria and 5 isolates of Gram-negative bacteria. The quantitative method we used to evaluate chitin-degrading enzyme activity measured the amount of N-acetylglucosamine produced from the reaction of crude enzyme and colloidal chitin. Seven isolates showing highest chitinolytic activity were Bacillus cereus (KKT 1, KKT 14, and KKT 19), Bacillus thuringiensis (KKT 6), Enterobacter cloacae (LCK 20), Pseudomonas stutzeri (LCK 17), and Stenotrophomonas maltophilia (THK1). The highest chitinolytic activity showed by KKT 1, KKT 6, KKT 14, KKT 19, and THK 1 were 0.0016 U/mL (at 72 hours); 0.0018 U/mL (at 48 hours); 0.0019 U/mL (at 48 hours); 0.0033 U/mL (at 48 hours); and 0.0032 U/mL (at 24 hours), respectively.
Keywords: chitinase activity; chitinolytic bacteria; shrimp rusip